Yeobo Topokki franchise business development strategy with business model canvas approach (Research, Society and Development, 2020)
Indonesians in general especially for younger generation, are more familiar with foreign cultures rather than being used to their own domestic culture, this phenomenon also occurred to the food aspect as a culture. This research aims to examine the development strategy of business model canvas approach in Yeobo Topokki franchise. The method used in this study is a descriptive business model, canvas model, and SWOT Analysis. The research was conducted in CV Usaha Anak Bangsa Perkasa which is located in Grand Depok City, Kalimulya, Depok, West Java. This study was conducted in April 2019 until December 2019. The results indicated that Yeobo Topokki accepted the business model improvement and the results of the strategy formulation that the company was in an aggressive position. Based on this analysis, it can be concluded that companies need to create value-added elements of the value proposition to create interest from prospective customers, such as by doing some certification on the products offered.